Cystic hygroma and esophageal atresia with tracheoesophageal fistula: Is there a genetic association? - Sravanthi Vutukuru; Nitin James Peters; Shivani Dogra; Ram Samujh (EL-Med-Pub, 2021)
Background: Tracheoesophageal fistula (TEF) is associated with many other congenital anomalies like cardiac, renal, and vertebral, but the association with cystic hygroma is very rare. Case Presentation: We report a neonate, antenatally diagnosed with cystic hygroma of the neck and incidentally diagnosed to have TEF. The baby was operated on after adequate stabilization and the cystic hygroma was managed with injection sclerotherapy. The genetic analysis for the FOX genes complex has been done in this case and the results showed no association between the two. Conclusion: There is a need for future studies to find out if the association between cystic hygroma and TEF is by chance or if any embryological or genetic cause can be attributed to it.